How Ease of Use, Convenience, Risk, Trust, and Security Affect Mobile Banking Use via Satisfaction - Suardana, I Wayan Arya; Mahyuni, Luh Putu (International Journal of Social Science and Business, 2024)
This study investigates the impact of ease of use, convenience, risk, trust, and security on the adoption of BNI ( Bank Negara Indonesia ) mobile banking, emphasizing the mediating role of customer satisfaction. The research is grounded in the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). Data were collected through a survey of 148 BNI mobile banking users in Bali and analyzed using Partial Least Squares (PLS). The findings reveal that convenience and security significantly influence customer satisfaction and the intention to use the application, with satisfaction partially mediating the relationship between convenience and intention. In contrast, ease of use, risk, and trust do not have a significant impact on satisfaction or intention. These results underline the critical role of convenience and security features in driving customer satisfaction and promoting the use of BNI mobile banking. To enhance the user experience, banks should focus on optimizing these aspects. Future studies could expand the scope by comparing these findings with those of other mobile banking platforms to identify the relative strengths and areas for improvement in BNI mobile banking services.